Winners or loser? Liberalizing public services - Rosskam, Ellen (Geneva, 2006)
Public services are being liberalized world wide, opened to foreign service providers, often turned into private services through privatization, commercialization, marketization, and deregulation. Yet the privatization of public services means that many, many people can no longer benefit from such services because they cannot pay, or because they do not belong to the social class for whom the private services are intended. Little is known about the changes taking place in services long-considered to be a public “right”, or about the widening social disparities that result from liberalization. What are the impacts on the social and economic security of employees in public services turned private? What happens to employees and “clients” when part of a public service turns private, effectively turning into “competition” for the public service? How rapidly is the liberalization of public services taking place, in which countries, and by what means? These are some of the questions this book attempts to answer through a state of the art review of the extent of the liberalization of public services around the world. Seven areas of public services are examined: health services (including mental health services and nursing home provision), secondary and higher education, pensions, public employment services, labour market training, criminal care services (particularly prisons), and social care services for children and the elderly. International experts in these seven areas of services provide insight into the mechanisms leveraging the liberalization of social services and the impacts on employees’ income security, employment security, labour market security, on health and working conditions, on opportunities for skills and career development, and on voice representation security. The book addresses questions of governance and makes policy recommendations for consideration by policy makers, employers, trade unions, civil society, academics, and international organisations. Issues discussed include the role played by international financial institutions, how foreign firms enter the market for provision of services, the impact of GATS on services, impact on clients receiving services and the impact of liberalization on the quality of service delivery. The research project was conducted jointly between the International Labour Office and Public Services International, the Global Union Federation of public service workers. Available upon request by emailing your name/address to: DISTR@ilo.org. Approx. 400 pages. Free of Charge. Available from ILO Geneva, July 2006.